Geomechanics for Energy and a Sustainable Environment - Cho, Gye-Chun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book describes recent advances in geomechanics for energy and the sustainable environment. Four research articles, related to high-level radioactive nuclear waste disposal stability, geological effect and wellbore stability considerations for methane gas hydrate production, and artificial soil freezing, are presented in this book. In addition, a comprehensive state-of-the-art review verifies the strong correlation between global climate change and the occurrence of geotechnical engineering hazards. The review also summarizes recent attempts to reduce CO2 emissions from civil and geotechnical engineering practices. Readers will gain ideas as to how we can deal with conventional and renewable energy sources and environment-related geotechnical engineering issues.